Film Animasi Edukasi Do’a Sebelum Tidur & Do’a Bangun Tidur Menggunakan Adobe Flash Cs6 - Wulandari; Asad; Haris (Universitas Mahakarya Asia, 2022)
A cartoon is a series of pictures taken of a moving object. The image is then projected onto a screen, and rotated at a certain speed to produce a live image. Currently, there are still many children who do not understand or know about the importance of praying and knowing the daily prayers, therefore the author tries to make an Educational Animation Film of Prayer Before Sleeping & Prayer of Waking Up Using Adobe Flash CS6 to Tk Bhaktitama Kec. Peninjauan. which aims to facilitate delivery through film. The data collection method used in the making of the Animation Educational Film for Prayer Before Sleeping & Prayer for Waking Up Using Adobe Flash CS6 at Bhaktitama Kindergarten, Kec. Review is the Reference method, the Interview method. The results of the final project research on a cartoon film entitled Making Animated Educational Films for Prayer Before Sleeping & Prayer for Waking Up Using Adobe Flash CS6.